Lop Ear to Conchal Microtia: An Algorithmic Surgical Approach. Issue 2 (February 2022) - Lese, Ioana; Aldabbas, Mohammed; Mazeed, Ahmed S.; Bulstrode, Neil W.
Abstract : Background: The lop ear deformity is defined by a deficient helix and scapha, underdeveloped anthelix, and downfolding of the helix. The terminology used is still confusing, and the treatment is not entirely structured. The aim of this study was to provide a new systematic surgical approach of this deformity based on our center's experience. Materials and Methods: All patients undergoing surgical correction of lop ears between 2007 and 2019 at Great Ormond Street Hospital were included. Patients' data, surgical techniques, and postoperative complications were recorded. Results: Based on our records, we identified 3 surgical techniques for the correction of lop ears, based on the degree of deformity encountered. In a mild lop ear, correction was achieved with a modified otoplasty technique by improving the definition of the antihelix and superior crus. In a moderate deformity, additional remodeling of the lidded helix was performed (extended otoplasty), whereas for the severe lop ear, the amount of cupping and the deficient cartilage required formal reconstruction using a carved rib cartilage framework. There were a total of 109 patients and 146 lop ears: 58 mild, 27 moderate, and 61 severe lop ears. Conclusion: We feel that there is a point in the spectrum of congenital ear deformity when a severe lop ear becomes a conchal microtia and recommend this approach to simplify the management of these cases. This is intended to bring greater clarity to how to deal with lop ears, based on the severity of the deformity and the surgical techniques used.